Fixed point of nonself total asymptotically nonexpansive mappings in Banach Spaces - Gunduz, Birol; Dutta, Hemen; Kilicman, Adem (Cornell University, 2017)
In this work, a new concept of nonself total asymptotically nonexpansive mapping is introduced and an iterative process is considered for two nonself totally asymptotically nonexpansive mappings. Weak and strong convergence theorems for computing common fixed points of two nonself total asymptotically nonexpansive mappings are established in the framework of Banach spaces. Finally, we give an example which show that our theorems are applicable.